2013
DOI: 10.1164/rccm.201211-2020oc
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Activated Protein C for Adults with Septic Shock. A Randomized Controlled Trial

Abstract: In adults with established and severe septic shock, DAA showed no evidence of benefit or harm. Clinical trial registered with www.clinicaltrials.gov (NCT00625209).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 21 publications
0
48
1
5
Order By: Relevance
“…7,8 However, none of the new adjunctive agents for sepsis therapy has improved survival rates in a consistent way. 9 The biology of sepsis includes inflammation, immune paralysis, apoptotic cell death, mitochondrial dysfunction, and microcirculatory derangement involving multiple pathways. Numerous studies have tested the efficacy and effectiveness of immunosuppression agents, but their impact has been frustratingly modest, and currently none is approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, none of the new adjunctive agents for sepsis therapy has improved survival rates in a consistent way. 9 The biology of sepsis includes inflammation, immune paralysis, apoptotic cell death, mitochondrial dysfunction, and microcirculatory derangement involving multiple pathways. Numerous studies have tested the efficacy and effectiveness of immunosuppression agents, but their impact has been frustratingly modest, and currently none is approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis reported by Kalil et al [18] in 2012 confirmed these results, with an 18% decrease in relative risk of mortality. Subsequently, however, two studies, performed by Annane et al [19] and Ranieri et al [20], respectively, showed that drotrecogin alfa (activated) provided no benefit in critically patients with septic shock and increased the severity of their illness. The use of drotrecogin alfa (activated) can no longer be recommended in the management of sepsis, no matter what its degree of severity.…”
Section: Drotrecogin Alfa (Activated)mentioning
confidence: 99%
“…Ciddi septik şok'lu yetişkinlerde, drotrecogin alfa aktive (DAA) fayda veya zararla ilgili hiçbir kanıt bulunmamıştır 26 .…”
Section: Vasopressör Ve İnotropik Destekunclassified